Are Heart Rate and Rating of Perceived Exertion Effective to Control Indoor Cycling Intensity? - Canário-Lemos, Rui (Int J Environ Res Public Health, 2020)
Indoor cycling’s popularity is related to the combination of music and exercise leading to higher levels of exercise intensity. It was our objective to determine the efficacy of heart rate and rating of perceived exertion in controlling the intensity of indoor cycling classes and to quantify their association with oxygen uptake. Twelve experienced males performed three indoor cycling sessions of 45 min that differed in the way the intensity was controlled: (i) oxygen uptake; (ii) heart rate; and (iii) rating of perceived exertion using the OMNI-Cycling. The oxygen uptake levels were significantly higher (p = 0.007; μ(p)(2) = 0.254) in oxygen uptake than heart rate sessions. Oxygen uptake related to body mass was significantly higher (p < 0.005) in the oxygen uptake sessions compared with other sessions. Strong correlations were observed between oxygen uptake mean in the oxygen uptake and rating of perceived exertion sessions (r =0.986, p < 0.0001) and between oxygen uptake mean in the oxygen uptake and heart rate sessions (r = 0.977, p < 0.0001). Both heart rate and rating of perceived exertion are effective in controlling the intensity of indoor cycling classes in experienced subjects. However, the use of rating of perceived exertion is easier to use and does not require special instrumentation.